Publishing Dissident Soviet Literature in Italy: The Case of Jaca Book (1966–1986) - Larocca, Giuseppina (Wiener Slawistischer Almanach, 2021)
This essay presents a panorama of Italian publishing from the 1960s to the 1960s in relation to the translation and dissemination of Russian and Soviet literature. Particular attention is paid to Jaca Book, an imprint founded in Milan in 1966 by university students. They had strong links with the Charles Peguy Catholic Center, which focused on translating dissident Russian and Soviet literature into Italian.